SYSTEMATIC MAPPING STUDY: ANALISIS MANAJEMEN PERUBAHAN PADA PERUSAHAAN KELUARGA - Raja Ainaya Alfatiha (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2022)
This study aims to conduct research mapping with the topic of discussion of change management (change management) in family companies (family business). This research includes a discussion of the research focus, research methods and types, and publication trends by country and time. This study uses a qualitative research method using the Systematic Mapping Study (SMS) to see the development of the research. Search data using the Scopus database and science direct with the results of 29 articles. Based on the mapping results, it is shown that the research focuses that are most often discussed are corporate governance, entrepreneurial, firm capability, and organizational development. The research method that is widely used is qualitative, namely 20 articles (69.0%). The dominant paper type used is the evaluation research category, namely 14 articles (48.3%). The publication trend of countries that do a lot of research is Italy, which is 4 articles (13.8%) and the peak of publication is in 2021 with 7 articles (24.1%). So that the results of this study can provide an overview and opportunity to explore new research topics related to change management and family companies